Analisis Kandungan Logam Berat Cu dan Zn dalam Air Limbah Industri - Asria, Merry; Alhamid, Fadila (Politeknik ATI Padang, 2020)
Industrial wastewater is water from the processing of an industrial process. This type of water is classified as having poor quality because of the contaminants it contains. The contaminants contained in industrial water vary depending on the related processes that produced the water. This study aims to determine the concentrations of heavy metals Cu and Zn in industrial wastewater at three locations in Batam City. Wastewater testing was carried out using the ICP-AES. The results obtained indicate that the levels of Cu and Zn in the industrial wastewater samples at the three locations are still below the maximum concentration limit permitted by the Environmental Quality Standards and are in accordance with the Regulation of the Minister of Environment of the Republic of Indonesia No. 5 of 2014 Annex 47 About Wastewater Quality Standards.